Correction: Gold(I) complexes based on six-membered phosphorus heterocycles as bio-active molecules against brain cancer - Rösch, Saskia; Fermi, Valentina; Rominger, Frank; Herold-Mende, Christel; Romero-Nieto, Carlos (Chemical communications, 2020)
Correction for ‘Gold(I) complexes based on six-membered phosphorus heterocycles as bio-active molecules against brain cancer’ by Saskia Roesch et al., Chem. Commun., 2020, DOI: 10.1039/d0cc05761d.
Gesehen am 03.02.2021